2014
DOI: 10.1590/s0100-69162014000500002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and treatment of sisal fiber residues for cement-based composite application

Abstract: ABSTRACT:Sisal fiber is an important agricultural product used in the manufacture of ropes, rugs and also as a reinforcement of polymeric or cement-based composites. However, during the fiber production process a large amount of residues is generated which currently have a low potential for commercial use. The aim of this study is to characterize the agricultural residues by the production and improvement of sisal fiber, called field bush and refugo and verify the potentiality of their use in the reinforcement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 19 publications
(13 reference statements)
5
14
0
2
Order By: Relevance
“…Some studies show that the coconut fibers have a larger diameter than sisal fibers. By Lima et al 66 , it was found that the average diameter of the sisal fibers was 280 µm ± 27 which is close to the value found in this study. Verma et al 67 showed that the diameter of the sisal fibers is a range of 50 to 200 µm, whereas the diameter of coconut fibers is in a range of 100-450 µm.…”
Section: Tensile Propertiessupporting
confidence: 90%
“…Some studies show that the coconut fibers have a larger diameter than sisal fibers. By Lima et al 66 , it was found that the average diameter of the sisal fibers was 280 µm ± 27 which is close to the value found in this study. Verma et al 67 showed that the diameter of the sisal fibers is a range of 50 to 200 µm, whereas the diameter of coconut fibers is in a range of 100-450 µm.…”
Section: Tensile Propertiessupporting
confidence: 90%
“…This thickness value is associated with the apparent diameter of the fiber, assuming a theoretical model in which the cross section is circular. However, it is known that the fiber section has multiple shapes and may vary along the length 23 . To reduce the error, sixty diameter measures were conducted for each treatment.…”
Section: Test Methodsmentioning
confidence: 99%
“…This property causes cause wood is not easy to be combined with non-organic materials such as hydrophobic (water-resistant) plastics. Combination of these two different properties materials will result in weak bond between fiber and matrix, and make it incompatible with a hydrophobic plastic matrix, due to the low wettability and weakness of the interface [4,5,6]. A weak bond between a hydrophilic fiber and a hydrophobic matrix can affect the physical and mechanical properties of the composite product.…”
Section: Introductionmentioning
confidence: 99%